Employing graphene acoustoelectric switch by dual surface acoustic wave transducers - Lee, Ching-Ping (Sci Rep, 2019)
We implement a logic switch by using a graphene acoustoelectric transducer at room temperature. We operate two pairs of inter-digital transducers (IDTs) to launch surface acoustic waves (SAWs) on a LiNbO(3) substrate and utilize graphene as a channel material to sustain acoustoelectric current I(ae) induced by SAWs. By cooperatively tuning the input power on the IDTs, we can manipulate the propagation direction of I(ae) such that the measured I(ae) can be deliberately controlled to be positive, negative, or even zero. We define the zero-crossing I(ae) as [Formula: see text] , and then demonstrate that I(ae) can be switched with a ratio [Formula: see text] at a rate up to few tens kHz. Our device with an accessible operation scheme provides a means to convert incoming acoustic waves modulated by digitized data sequence onto electric signals with frequency band suitable for digital audio modulation. Consequently, it could potentially open a route for developing graphene-based logic devices in large-scale integration electronics.